Citrus aurantium flavonoids inhibit adipogenesis through the Akt signaling pathway in 3T3-L1 cells - Kim Gon-Sup; Park Hyoung Joon; Woo Jong-Hwa; Kim Mi-Kyeong; Koh Phil-Ok; Min Wongi; Ko Yeoung-Gyu; Kim Chung-Hei; Won Chung-Kil; Cho Jae-Hyeon (BMC, 2012)
Abstract Background Obesity is a health hazard that is associated with a number of diseases and metabolic abnormalities, such as type-2 diabetes, hypertension, dyslipidemia, and coronary heart disease. In the current study, we investigated the effects of Citrus aurantium flavonoids (CAF) on the inhibition of adipogenesis and adipocyte differentiation in 3T3-L1 cells. Methods During adipocyte differentiation, 3T3-L1 cells were treated with 0, 10, and 50 μg/ml CAF, and then the mRNA and protein expression of adipogenesis-related genes was assayed. We examined the effect of CAF on level of phosphorylated Akt in 3T3-L1 cells treated with CAF at various concentrations during adipocyte differentiation. Results The insulin-induced expression of C/EBPβ and PPARγ mRNA and protein were significantly down-regulated in a dose-dependent manner following CAF treatment. CAF also dramatically decreased the expression of C/EBPα, which is essential for the acquisition of insulin sensitivity by adipocytes. Moreover, the expression of the aP2 and FAS genes, which are involved in lipid metabolism, decreased dramatically upon treatment with CAF. Interestingly, CAF diminished the insulin-stimulated serine phosphorylation of Akt (Ser473) and GSK3β (Ser9), which may reduce glucose uptake in response to insulin and lipid accumulation. Furthermore, CAF not only inhibited triglyceride accumulation during adipogenesis but also contributed to the lipolysis of adipocytes. Conclusions In the present study, we demonstrate that CAF suppressed adipogenesis in 3T3-L1 adipocytes. Our results indicated that CAF down-regulates the expression of C/EBPβ and subsequently inhibits the activation of PPARγ and C/EBPα. The anti-adipogenic activity of CAF was mediated by the inhibition of Akt activation and GSK3β phosphorylation, which induced the down-regulation of lipid accumulation and lipid metabolizing genes, ultimately inhibiting adipocyte differentiation.